Conflicting values: ecosystem services and invasive tree management - Dickie, Ian A. (2014)
Tree species have been planted widely beyond their native ranges to provide or enhance ecosystem services such as timber and fibre produc- tion, erosion control, and aesthetic or amenity benefits. At the same time, non-native tree species can have strongly negative impacts on ecosystem services when they naturalize and subsequently become invasive and disrupt or transform communities and ecosystems. The dichotomy between positive and negative effects on ecosystem services has led to significant conflicts over the removal of non-native invasive tree species worldwide. These conflicts are often viewed in only a local context but we suggest that a global synthesis sheds important light on the dimensions of the phenomenon. We collated examples of conflict sur- rounding the control or management of tree invasions where conflict has caused delay, increased cost, or cessation of projects aimed at invasive tree removal. We found that conflicts span a diverse range of taxa, systems and countries, and that most conflicts mergearound three areas: urban and near-urban trees; trees that provide direct economic benefits; and invasive trees that are used by native species for habitat or food. We suggest that such conflict should be seen as a normal occurrence in invasive tree removal. Assessing both positive and negative effects of invasive species on multiple ecosystem services may provide a useful framework for the resolution of conflicts